Improving Memory Efficiency on Android: Leveraging Data Structures for Optimal Performance - Mafmudin, Muchamad; Harnaningrum, Lucia Nugraheni (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2025)
This study discusses strategies for increasing memory efficiency in Android application development using optimal data structures. In the era of growing mobile device usage, especially in Indonesia, where the number of users exceeds the total population, memory management has become a major challenge for Android developers. This study analyzes various data structures such as List, ArrayList, MutableList, and LinkedList, as well as comparisons between object and primitive data types in Kotlin. The results show that primitive data structures offer better memory efficiency and execution time than object-based data structures due to their simpler structure and lower complexity. Meanwhile, object data types like MutableList and ArrayList are more efficient for applications that require a balance between flexibility and performance, as they provide both primitive-like characteristics and useful built-in functions. This study also emphasizes the importance of understanding memory management and time complexity in optimizing Android application performance. Testing was conducted using both automated and manual methods. The findings show that Kotlin reduces memory usage by up to 2× and execution time by 28.6% compared to Java. Among the evaluated structures, primitive arrays and LinkedLists showed the most stable memory performance, while MutableLists offered the best balance for object types.